Hypergravity Stimulation Enhances PC12 Neuron-Like Cell Differentiation - Genchi, Giada Graziana (Biomed Res Int, 2015)
Altered gravity is a strong physical cue able to elicit different cellular responses, representing a largely uninvestigated opportunity for tissue engineering/regenerative medicine applications. Our recent studies have shown that both proliferation and differentiation of C2C12 skeletal muscle cells can be enhanced by hypergravity treatment; given these results, PC12 neuron-like cells were chosen to test the hypothesis that hypergravity stimulation might also affect the behavior of neuronal cells, in particular promoting an enhanced differentiated phenotype. PC12 cells were thus cultured under differentiating conditions for either 12 h or 72 h before being stimulated with different values of hypergravity (50 g and 150 g). Effects of hypergravity were evaluated at transcriptional level 1 h and 48 h after the stimulation, and at protein level 48 h from hypergravity exposure, to assess its influence on neurite development over increasing differentiation times. PC12 differentiation resulted strongly affected by the hypergravity treatments; in particular, neurite length was significantly enhanced after exposure to high acceleration values. The achieved results suggest that hypergravity might induce a faster and higher neuronal differentiation and encourage further investigations on the potential of hypergravity in the preparation of cellular constructs for regenerative medicine and tissue engineering purposes.